SIMPLIFIED HATCHERY TECHNIQUE FOR MASS PRODUCTION OF PENAEID PRAWN SEED USING FORMULA FEED - Mohamed, K H; Muthu, M S; Pillai, N N; Pandian, S K (Indian Journal of Fisheries, 2011)
A techaique for large-scale production of penaeid prawn seed using a dry microparticulate formula feed, NPCL-17, is described. The details of preparing the feed which is compounded from inexpensive, locally available raw materials such as groundnut oil cake, fish meal, dried mantis shrimp, prawn waste and tapioca and fortified with vitamins and minerals are given. The larvae are grown in outdoor tanks filled with 2 m’ of seawater, filtered through 60-micron mesh nylobolt cloth. The daily ration of formula feed is offered in 4 equal instalments at 6 hourly intervals and the larval tanks are vigorously aerated. Apart from providing nutrition for the larvae, the feed, under the influence of sunlight, helps to create a natural ecosystem conducive for their survival. The easy-to-dispense dry feed has greatly simplified the larval rearing procedures and has given an average survival* rate of 66.7% from nauplius to postlarva. The rationale of the feeding schedules and the particle size of the feed offered are discussed in the light of the changes taking place in the functional morphology of the feeding appendages during larval development